Description of four new species of Limnadopsis from Australia (Crustacea: Branchiopoda: Spinicaudata) - Schwentner, Martin; Timms, Brian V.; Richter, Stefan (Zootaxa, 2012)
Four new species of Limnadopsis, L. bloodwoodensis sp. nov., L. paratatei sp. nov., L. brevirostris sp. nov. and L. centralensissp. nov., are described for Australia. Three of these were delineated in an earlier study based on an integrative taxonomicapproach. The fourth (L. centralensis sp. nov.) was not part of that study but can be distinguished from all other Limnadopsismorphologically. The morphological variation in L. tatei is described here in detail as L. paratatei sp. nov. and L. tatei closely resemble each other and have in earlier studies been grouped together as L. tatei.